Peran motivasi belajar dan disiplin belajar pada prestasi belajar mata pelajaran prakarya dan kewirausahaan - Azeti, Senja; Mulyadi, Hari; Purnama, Ridwan (Business Education Program of Universitas Pendidikan Indonesia, 2019)
The aim of the research is to find out the influence of learning motivations on study achievement and the influence of learning discipline on study achievement. The object used as analysis unit on this research is vocational students in Bandung regency. Verification process applied in this study by using explanatory research for 123 respondents. The results showed correlation between learning motivation and academic achievement, majority of the high school students were motivatedly enough by academic achievement. Again, there was a significant correlation between learning discipline and academic achievement. The study also found that, Learning discipline has impactful effect on academic achievement. The study showed that, academic achievement increased by arise learning motivation, and while the students are discipline, it will scale-up academic achievement.